TRANSDERMAL PATCH-BASED DELIVERY OF TIRZEPATIDE: A CONTROLLED RELEASE STRATEGY FOR DIABETES TREATMENT - PARUL NIGAM; ANUSHKA VERMA; SAYANTAN DUTTA (Innovare Journal of Medical Sciences, 2025)
This thorough analysis explores the paradigm change brought about by transdermal patches filled with tripeptide, a potential therapeutic agent, at a time when the prevalence of diabetes is rising quickly and calls for creative and efficient treatment options. The diabetes management environment is challenging, calling for a transformational strategy. An appealing option that delivers continuous release, less side effects, and improved patient adherence is transdermal medication administration. Trizipatide, a new diabetes therapy agent, affects insulin sensitivity and glucose metabolism. The formulation of trizipatide-loaded transdermal patches is thoroughly examined in this review, which also explains the patch’s composition and production techniques. This review elucidates the effectiveness of these patches by thoroughly analyzing in vitro and in vivo research, highlighting their ability to maintain stable blood glucose levels, reduce hypoglycemia, and improve overall glycemic management. Addressing issues with skin variability and patch adherence is essential for a successful clinical application. The assessment also points to potential future developments in diabetes care, such as personalized therapy and the incorporation of cutting-edge technology, such as continuous monitoring systems and microneedle-based patches. In conclusion, trizipatide transdermal patches show considerable promise in addressing the drawbacks of traditional diabetes management, ushering in an easy-to-use therapeutic strategy with transformative potential while highlighting the need for regulatory considerations and long-term safety evaluation in this novel journey toward improved diabetes care. This review is intended for a wide readership, including academics, medical professionals, and decision-makers involved in the rapidly developing field of transdermal drug delivery for the treatment of diabetes.